The Right to be Forgotten and the Media - Ovčak Kos Maja (LeXonomica, 2019)
The right to be forgotten is not the right to a “perfect” past, but provides some control over one’s personal information on the Internet under certain conditions. Its content and scope cannot be defined precisely, but its essence is undoubtedly the individual’s entitlement, based primarily on the right to respect one’s private and family life, to request erasure of personal data or information on the basis of which an individual can be identified against any controller. The right to be forgotten is a legal concept still at the beginning of its development, and case law will have to play a decisive role in shaping its content. An important limitation on the right to be forgotten is the passive aspect of the right to freedom of expression. Therefore, in the case of media contributions, the restriction on the exercise of the right to be forgotten is justified by particularly strong, substantiated reasons. In resolving the conflict between the right to be forgotten and the freedom of media expression, it is necessary to proceed from criteria which, regarding the conflict between Articles 8 and 10 of the ECHR were set up by the ECtHR.